The Influence of Activity Ratios, Company Size, and Leverage on Stock Returns in Pharmaceutical Sector Manufacturing Companies Listed on the Indonesian Stock Exchange for the 2018–2021 Period - Wiliam Wiliam; Dzulfa Khairuna; Tesalonika Bawamenewi; Mikka Terayani Siregar; Hendra Saputra (Cita konsultindo, 2024)
The objective of this study is to examine the individual and combined effects of activity ratio (TATO), Company Size, and leverage (DER) on stock returns. This study incorporates quantitative descriptive research. The population consisted of 36 enterprises involved in the production of pharmaceutical products. The study focused on a sample of 9 companies, observed over a period of 4 years. The statistical technique employed is multiple linear regression analysis. The research findings indicate that the classical assumptions have fulfilled the necessary criteria. The t-test analysis reveals that both Partially Total Asset Turnover and Company Size have a negative and statistically negligible impact on stock returns. However, it is shown that DER does not have any affect on stock returns. Concurrently, the f test indicates that all independent variables have no effect and are not correlated with stock returns.